Evaluación de las contusiones y del pH en canales bovinas en un matadero de la provincia de Santa Fe - Tuninetti, N. (2017)
Bruises cause major economic losses in the bovine industry as they negatively impact on meat quality and they are important sources of information on animal welfare. Moreover, they reflect flaws in management practices, poor infrastructure design and unskilled personnel. Meat with high pH values results from glycogen repletion prior to slaughter and the consequent inability to accumulate lactic acid. As regards its appearance, it is dark, firm and dry (DFD) and less soft. It also has palatability defects and it facilitates the development of microorganisms, thus being little appreciated by consumers. The presence of bruises and the aspects related to alterations in meat quality, such as high pH, were observed in 300 bovine carcasses, mostly heifers. In the lumbar region of the Longissimus dorsi muscle, pH was determined 24 h after slaughter. Over 99% of the carcasses showed at least one bruise, the average number of bruises per carcass was 7.39 and a 69% of the carcasses had at least six bruises. An 89.8% of the bruises had irregular form and an 88.3% a rose-red color. Bruises sized 8-16 cm were the most commonly found. Over 90% of the bruises were grade one or superficial. There was a prevalence of bruises on the plate (46.5%), and the rest were observed on ribs and abdomen (26.1%), on legs (19.9%) and on the back (7.5%). There was a higher number of lesions in adult animals than in young ones, and in female and castrated animals than in male intact animals. The average range of pH values was 5.59 ± 0,29. An 83.3% of the sampled animals had a pH below or equal to 5.79, an 11.7% had a pH in a range between 5.80 and 5.99 and the remaining 5% were above pH 6. Our results suggest that there are serious management problems affecting animal welfare and carcass quality, indicating that most bruises take place after animals leave production establishments. A prolonged resting time appears to be a critical issue in our study as regards bruising and high meat pH. It is necessary that both authorities and also the personnel in companies become aware of the importance of improving abattoir infrastructure, training personnel and applying proper animal welfare norms in order to minimize animal and carcass damage that result from bruising.\n